2021
DOI: 10.1017/s1431927621001288
|View full text |Cite
|
Sign up to set email alerts
|

Real-time interactive ptychography from electron event representation data

Abstract: The arrival of direct electron detectors (DED) with high frame-rates in the field of scanning transmission electron microscopy has enabled many experimental techniques that require the collection of a full diffraction pattern at each scan position, a field which is subsumed under the name 4D-STEM.DED frame rates approaching 100kHz place stringent requirements on data transmission rates and computing infrastructure. Current commercial DEDs allow the user to make compromises in pixel bit depth, detector binning … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Crop-outs containing only the scan positions covering the Zr 11 Te 50 DW-CNT for all tilts were determined from annular bright-field images (12.5 mrad-25 mrad integration range) of the tilt series for ptychographic reconstruction. Initial guesses for the defocus aberration for each tilt were manually obtained with an interactive real-time implementation 28 of the single-sideband ptychography method 67 . The data in EER format was further preprocessed by centering the position-averaged diffraction pattern, symmetric cropping to a maximum detector angle of 2Ξ±, with Ξ± the semi-convergence angle, and binning to a detector size of 88 Γ— 88 pixels.…”
Section: Ptychographic Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop-outs containing only the scan positions covering the Zr 11 Te 50 DW-CNT for all tilts were determined from annular bright-field images (12.5 mrad-25 mrad integration range) of the tilt series for ptychographic reconstruction. Initial guesses for the defocus aberration for each tilt were manually obtained with an interactive real-time implementation 28 of the single-sideband ptychography method 67 . The data in EER format was further preprocessed by centering the position-averaged diffraction pattern, symmetric cropping to a maximum detector angle of 2Ξ±, with Ξ± the semi-convergence angle, and binning to a detector size of 88 Γ— 88 pixels.…”
Section: Ptychographic Reconstructionmentioning
confidence: 99%
“…It can be implemented as a direct phase-retrieval method [22][23][24] or using iterative phase-retrieval algorithms 25,26 using many different experimental configurations 27 . Direct ptychography methods enjoy a low computational complexity and can provide real-time feedback when implemented on modern hardware 28 , while iterative ptychography algorithms allow to jointly solve for the complex sample transmission function 29 , a non-parametric probe wave function 30,31 , sub-pixel scan positions 32,33 , partial coherence effects in the experiment 33,34 , fluctuating illumination during the scan 35 and can provide superior resolution and reconstruction quality under certain conditions 33,36 . Neural-network-based reconstruction methods improve the aforementioned direct methods while retaining real-time reconstruction capabilities 37,38 .…”
mentioning
confidence: 99%
“…Ophus et al have demonstrated that the py4DSTEM package can be integrated with microscope data acquisition for automated crystallographic orientation mapping [62]. In another example, it was demonstrated that the obtained 4D-STEM datasets can be used to perform single sideband (SSB) ptychography [63] in real time by using GPUbased solvers on a connected edge system [64,65].…”
Section: Ongoing Edge-computing-enabled Automated Electron Microscopy...mentioning
confidence: 99%
“…One of the most important hardware improvements of the last few years has been the development of high-speed direct electron detectors capable of capturing diffraction patterns 𝐼𝐼(π‘˜π‘˜ π‘₯π‘₯ , π‘˜π‘˜ 𝑦𝑦 ) as a function of probe position (π‘Ÿπ‘Ÿ π‘₯π‘₯ , π‘Ÿπ‘Ÿ 𝑦𝑦 ), yielding a 4-dimensional (4D-STEM) dataset, Figure 1a. [1][2][3][4][5] These spatially resolved diffraction patterns can be used to generate a virtually unlimited number of images by making use of various scattering regimes and more advanced post-processing, such as centre-of-mass imaging, electron ptychography, strain mapping, and virtual dark field, to name a few. [6] State-of-the-art 4D-STEM detectors typically compromise on number of pixels (10 4 to 10 7 pixels), frame rate (10 2 to >10 5 ), and dynamic range (10s to >10 6 electrons), depending on the intended use cases.…”
mentioning
confidence: 99%